Memperbaiki Drop Tegangan dengan Simulasi Rekonfigurasi Jaringan Sistem 20 kV - Surya Ekanugraha; Ali Basrah Pulungan (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
The Gardu Hubung (GH) that uses one Express Refiner will result in a lack of maneuvering points on the 20 kV system, resulting in blackouts with a long duration of outages. The outage affected the magnitude of Energy Not Sold (ENS). The sale of electrical energy that is not maximal will cause a decrease in the image of PT. PLN (Persero) in the eyes of the public. ENS problems can be overcome by reconfiguring the network. This study was conducted on GH Balitan located in Dhamasraya Regency. Network reconfiguration is done using simulations by adding one Incoming from The New Express Turtle from Gardu Induk (GI) Sungai Rumbai Trafo Daya (TD) one. Based on the results of the simulation, the voltage value rose in GH Balitan from 18.60 kV to 20.14 kV. The results obtained show that network reconfiguration can improve the voltage value. This voltage drop improvement shows an increase in the reliability of the 20 kV GH Balitan system.